Audit Energi dan Peluang Penghematan Energi dengan Metode ANP-PROMETHEE : Studi Kasus : Trio Plaza Magelang - Nadia Aulia Shidqi; Deria Pravitasari; Hery Teguh Setiawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Trio Plaza Magelang is a shopping center that sells household needs. The energy audit in this study was focused on the lighting system. The purpose of this research is to find out the level of electrical energy consumption and to choose the best recommendation for electricity saving opportunities. And the results of the audit of electrical energy consumption at Trio Plaza Magelang obtained the total energy consumption value for the lighting system load of 7480 kWh/month, and supporting equipment loads of 18,316 kWh/month and the total value of Tno Plaza’s energy consumption reached 25 796 kWh/month. energy saving using the ANP-PROMETHEE method.